Generación de energía eléctrica a partir de aguas residuales por medio de celdas de combustible microbiano (2024)
In the constant search for sustainable and environmentally friendly energy sources, the generation of electrical energy from microbial fuel cells has emerged as a promising alternative. This innovative approach harnesses the metabolic activity of microorganisms to convert organic matter into electricity, offering a renewable and efficient method. Throughout this work, we will explore various alternatives in the energy generation process using microbial fuel cells, comparatively evaluating their efficiency and highlighting the advantages and disadvantages inherent to each approach.